Familial Idiopathic Basal Ganglia Calcification: A Father-Son Dyad Demonstrate Heterogeneity of Presentation and Disease Progression. (23rd April 2021) - Zahniser, Evan; Bird, Thomas D; Chen, Dong-Hui; Hu, Shu-Ching; Raskind, Wendy H; Trittschuh, Emily H
Abstract: Objective: Familial idiopathic basal ganglia calcification (FIBGC) is a rare, heritable disease characterized by calcium deposition in the basal ganglia and other brain regions. Clinical presentations are diverse, featuring an array of neurologic, psychiatric, and/or cognitive symptoms. This dyad report presents neurogenetic, neuroimaging, neurological, and serial neuropsychological data from a father (S1) and son (S2) with FIBGC. Method/Results: The SLC20A2 genetic mutation c.1828-1831delTCCC was identified for each patient, both of whom evidenced similar patterns of brain calcification mainly in the basal ganglia and cerebellum on neuroimaging. S1's onset was in his late 60s with primary motor abnormalities followed by cognitive decline; S2's younger onset (late 30s) was characterized by predominant psychiatric symptoms and mild cognitive changes. Our unique, detailed longitudinal study revealed that both subjects demonstrated largely stable performance across most neuropsychological domains assessed. Conclusions: The subjects' differences in presentation demonstrate the variable expressivity in FIBGC even with the same pathogenic variant within a single family. Distinct phenotypes may be associated with age of onset even in persons with the same mutation, consistent with past research. Disease progression may feature an initial period of notable change from baseline followed by relative stability, as seen both on imaging and neuropsychological evaluation.